PENGARUH LATIHAN DRILL HORIZONTAL SWINGS TERHADAP POWER OTOT LENGAN DAN BAHU PADA TIM PUTRA TENIS MEJA SMA OLAHRAGA PEKANBARU - M. Fakhrur Rohman; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem of this study is the arm and shoulder muscle power on SMA Olahraga Pekanbaru men’s table tennis team, when doing drill horizontal swings researchers see still lack in arm muscle strength. This is clearly seen during practice and competition. Where athletes do matches with balanced opponents and play by looking for 3 wins, athletes are less than optimal in making smash because of lack of arm and shoulder muscle strength in these athletes so that when making a ball the ball always does not make it over the net, and even on the net lip so the ball falls on their own field and tends to lose athletes. The purpose of this study was to determine whether there is an effect of exercise on the Drill Horizontal Swings on Arm and Shoulder Muscle Power on SMa Olahraga Pekanbaru Men’s Table Tennis Team. This research was conducted at SMA Olahraga Pekanbaru. When the study was conducted on 10 December 2019 to 20 January 2020. Given the relatively small number of samples, in this study the entire population was sampled. Thus the determination of the sample uses a total sampling technique (saturated sample) in which the entire population is sampled as many as 6 people on SMA Olahraga Pekanbaru Men’s Table Tennis Team. Based on the results of research and data processing can be concluded as follows: there is a significant effect of drill horizontal swings exercise (X) with an increase in arm and shoulder muscle power (Y) on SMA Olahraga Pekanbaru men's table tennis team. These results are indicated by the following research data: the amount of pretest data is 29.62 with an average value of 4.93 and the amount of post test data is 40.58 with an average value of 6.76. Then the ‘t’ test analysis yields a tcount of 16.54 and a table of 2.015. Means tcount (16.54)> ttable (2,015). It can be concluded that there is a significant the effect of drill horizontal swings training on SMA Olahraga men's table tennis team . Key Words: Effect of Drill Horizontal Swings Exercise, Arm and Shoulder Muscle Power